AN APPROACH TO MODELING INNOVATION OBSOLESCENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Currently, the Fourth Industrial Revolution (FIR) has a very strong impact on innovation activity and innovation obsolescence. In order to formulate a methodology for the selection of alternative solutions, it is necessary not only to take into account the impacts of FIR, but also to choose an approach for modeling innovation obsolescence. The aim is to propose a new approach for modeling innovation obsolescence, in which the influencing factors will already be present in the innovation development methodology.